Target and non-target response of Swietenia Mahagoni Jacq. chemical constituents against tobacco cutworm Spodoptera litura Fab. and earthworm, Eudrilus eugeniae Kinb. (May 2018) - Dinesh-Kumar, Anandan; Srimaan, Elangovan; Chellappandian, Muthiah; Vasantha-Srinivasan, Prabhakaran; Karthi, Sengodan; Thanigaivel, Annamalai; Ponsankar, Athirstam; Muthu-Pandian Chanthini, Kanagaraj; Shyam-Sundar, Narayanan; Annamalai, Mahendiran; Kalaivani, Kandaswamy; Hunter, Wayne B.; et al.
Abstract: Toxicological screening of Swietenia mahagoni Jacq. (Meliaceae, West Indies Mahogany) against the lepidopteran pest Spodoptera litura was examined. Phytochemical screening through GC-MS analysis revealed nine peaks with prominent peak area % in Bis (2-ethylhexyl) phthalate (31.5%) was observed. The larvae exposed to discriminating dosage of 100 ppm deliver significant mortality rate compare to other treatment concentrations. The lethal concentrations (LC50 and LC90 ) was observed at the dosage of 31.04 and 86.82 ppm respectively. Sub-lethal concentrations (30 ppm) showed higher larval and pupal durations. However, pupal weight and mean fecundity rate reduced significantly. Similarly, the adult longevity reduced significantly in dose dependent manner. Midgut histology studies showed that the methanolic extracts significantly disturbs the gut epithelial layer, lumen and brush border membrane compare to the control. The soil assay on a non-target beneficial organism, the soil indicator earthworm Eudrilus eugeniae, with extracts from S. mahagoni (200 mg/kg) showed no toxicity compared to Monocrotophos at the dosage of 10 ppm/kg. Current results suggest that this bio-rational plant product from S. mahagoni displays a significant effect to reduce lepidopteran pests with low toxicity to other beneficial species. Highlights: Toxicological screening of Swietenia mahagoni Jacq. against the lepidopteran pest Spodoptera litura. The lethal concentration (LC50 and LC90 ) was observed at the dosage of 31.04 and 86.82 ppm respectively. Sub-lethal concentrations (30 ppm) showed higher larval and pupal durations. Midgut histology showed that methanolic extracts significantly disturbs the gut epithelial layer, lumen and brush border membrane. Bio-rational plant product from S. mahagoni displays a significant effect to reduce lepidopteran pests.